Prominence matching in english songs : a historical perspective - Proto, Teresa (Signa: Revista de la Asociación Española de Semiótica, 2013)
La poesía métrica es la fuente primaria de evidencia lingüística para la reconstrucción del sistema de acentuación de una lengua muerta, y en particular la métrica que controla la coincidencia o ajuste entre acento lingüístico y posiciones fuertes. para el inglés medio, la distribución del acento léxico a través de los esquemas débil/fuerte del pentámetro yámbico, desde chaucer hasta shakespeare, ha ofrecido información importante para el análisis lingüístico. además de la poesía hablada, las canciones proveen otro tipo de poesía métrica presente en este periodo que, sin embargo, aún no ha sido explotado como fuente de evidencia métrica o lingüística. el presente trabajo intenta contribuir a llenar este vacío a través del estudio diacrónico del desajuste prominente. The primary source of linguistic evidence in reconstructing stress systems is provided by metered poetry, particularly by meters that control the matching of the linguistic stress to metrical strong positions. For middle english, the distribution of lexical stress across the weak/strong patterns of iambic pentameter, from chaucer to shakespeare, has provided important clues for linguistic analysis. in addition to spoken poetry, songs provide another type of metered poetry from that period. however, they have not been exploited as a source of metrical or linguistic evidence. the present paper takes a tentative step towards filling this gap, by focusing on a diachronic study of prominence mismatching.